(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The study of Abai’s work in the aspect of his artistic world is currently one of the relevant issues of both Abai studies and interdisciplinary research. Comprehension of this issue under the phenomena of reality and psychology of the processes of poet’s artistic thinking is of an important social significance. The given article examines the issues of artistic world of Abai. Artistic world of Abai is a world of literary art. The basis for his literary art comes from the real world. The great genius creates the work of verbal art based on the events of the real world and its phenomena. A work of verbal art is neither reality nor the mirror image of it. The world of an art work is a possible world, a result of unique creative performance of an individual. Comprehension of the poet’s art world, his relation to reality requires a special study and serious scientific approach. The meaning of the phenomena of reality reflected in Abai’s artistic world is profound. The variety of semantic definitions, cognitive-semiological richness of the poet’s expressive means characterize his artistic world as a world of high poetic wisdom.